2018
DOI: 10.1155/2018/9597158
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Metaheuristic Artificial Immune System for Household Energy Optimization

Abstract: Devices in a smart home should be connected in an optimal way; this helps save energy and money. Among numerous optimization models that can be found in the literature, we would like to highlight artificial immune systems, which use special bioinspired algorithms to solve optimization problems effectively. The aim of this work is to present the application of an artificial immune system in the context of different energy optimization problems. Likewise, a case study is performed in which an artificial immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
0
2
0
2
Order By: Relevance
“…Furthermore, AIS has demonstrated efficiency in convergence compared to other algorithms for large instances. The authors of [44][45][46][47][48][49] reported that AIS has a higher convergence rate than GA, PSO, AC, and SA. Therefore, AIS is used to solve our model for large-sized instances for all the reasons above.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, AIS has demonstrated efficiency in convergence compared to other algorithms for large instances. The authors of [44][45][46][47][48][49] reported that AIS has a higher convergence rate than GA, PSO, AC, and SA. Therefore, AIS is used to solve our model for large-sized instances for all the reasons above.…”
Section: Related Workmentioning
confidence: 99%
“…The method of artificial immune systems is used to solve optimization and optimal control problems. In [29,30], solutions of optimization problems in power engineering and power systems based on the method of artificial immune systems are presented. In [31,32] the application of artificial immune system for solving optimization problems of multimodal functions is considered.…”
Section: Introductionmentioning
confidence: 99%
“…показано контурний графік залежності цільової функції за(14) в просторі координат «кількість груп» та «максимальна кількості програшів» при мінімізації двовимірних функцій. Можна побачити, що при збільшенні кожної з величин понад 5, цільова функція значно зростає за рахунок збільшення кількості ітерацій.На рис.…”
unclassified
“…Можна побачити, що при збільшенні кожної з величин понад 5, цільова функція значно зростає за рахунок збільшення кількості ітерацій.На рис. 2 показано графік та контурний графік залежності цільової функції за(14) в просторі координат «періодичність міжгрупового стиснення» та «періодичність внутрішньогрупового стиснення» при розв'язанні тестових задач у 8-вимірному просторі. З графіка можна помітити, що залежність має один екстремум при сполученні значень трохи більше 10.…”
unclassified